Scientific Rationale for RPE Use in Fitness Assessment and Exercise Participation. (July 2020) - Kilpatrick, Marcus; Newsome, A'Naja; Foster, Carl; Robertson, Robert; Green, Matt
Abstract : Apply It!: Fitness professionals will learn the different ways that RPE scales can be used. Fitness professionals will have newfound confidence in the importance of regulating exercise by using RPE scales. Fitness professionals will be able to properly use RPE scales during exercise testing and prescription. Abstract : Ratings of perceived exertion (RPEs) have a long history of use in the world of fitness. The effective use of these tools by clinicians and practitioners can optimize patient and client outcomes.